2018
DOI: 10.1021/acs.chemmater.7b03986
|View full text |Cite
|
Sign up to set email alerts
|

Fast Lithium-Ion Conduction in Atom-Deficient closo-Type Complex Hydride Solid Electrolytes

Abstract: closo-type complex hydrides contain large cage-type complex polyanions in their crystal structures and thus can exhibit superior ion-conducting properties (e.g., Li and Na). However, the unique structures of complex polyanions have made it challenging to modify crystal structures, making systematic control of ion conductivity difficult. Here, we report an atom deficiency approach to enhance lithium-ion conductivity of complex hydrides. We find that lithium and hydrogen could be simultaneously extracted from Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 36 publications
2
70
0
Order By: Relevance
“…By contrast, both Li 2 B 10 H 10 and Li 2 B 12 H 12 have much higher transition temperatures in excess of 600 K, restricting their high ionic conductivities. Recently, however, it was found that the ball milled Li 2 B 12 H 12 sample showed an exceptionally high ionic conductivity of 3.1 × 10 −4 S cm −1 at room temperature . It was suggested that such an enhancement was related to the effect of borane impurities present in the sample via mechanochemical treatment, leading to mixed borane disordered phase with high ionic conductivity 1b…”
Section: Complex Hydrides As Solid‐state Electrolytementioning
confidence: 99%
“…By contrast, both Li 2 B 10 H 10 and Li 2 B 12 H 12 have much higher transition temperatures in excess of 600 K, restricting their high ionic conductivities. Recently, however, it was found that the ball milled Li 2 B 12 H 12 sample showed an exceptionally high ionic conductivity of 3.1 × 10 −4 S cm −1 at room temperature . It was suggested that such an enhancement was related to the effect of borane impurities present in the sample via mechanochemical treatment, leading to mixed borane disordered phase with high ionic conductivity 1b…”
Section: Complex Hydrides As Solid‐state Electrolytementioning
confidence: 99%
“…Among the various materials reported to date, complex borohydrides are considered outstanding potential candidates for the solid electrolyte in SSBs because of the high Li-or Na-ion conductivity (exceeding 10 −1 S cm −1 ) [12][13][14][15][16][17][18][19][20], which enables a wide range of chemical substitutions and opens up the possibility of searching for even better ion-conductive materials. The general form of metal borohydrides is written as M x (M y H z ), where M can be replaced by alkali or alkaline-earth atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The general form of metal borohydrides is written as M x (M y H z ), where M can be replaced by alkali or alkaline-earth atoms. Typical complex M y H z anions include BH − 4 [21,22], B 6 H 6 2− , B 10 H 10 2− , CB 9 H 10 − , B 12 H 12 2− , and CB 11 H 12 − [19]. Among the cations, lithium-ion electrolytes are a key component of all SSBs.…”
Section: Introductionmentioning
confidence: 99%
“…S6). These results would originate from the structural deviations such as the change in the lithium arrangements, which can lead to a higher carrier concentration in the former than in the latter [15] . Second, the ionic conductivity can increase by changes in the lattice size.…”
Section: Resultsmentioning
confidence: 99%
“…Closo -type complex hydrides, with ion conductivities approaching 10 −1 S cm −1 in their high-T phases, have also been intensively investigated [12][13][14][15] . Unlike LiBH 4 -based compounds, the complex anions in closo -type complex hydrides comprise not only multiple hydrogen atoms but also multiple boron (and carbon) atoms.…”
Section: Introductionmentioning
confidence: 99%